Information technology in future education: open and distance learning - Khalifa, Othman Omran (2003)
Globalization challenges the developing countries to catch up and to set up a institutionalize a system of educational planning that will produce skilled manpower and knowledge workers required for today and future. The introduction of information technology and communication are enhancing the delivery of education, changing the roles of students and teachers, and producing a shift in society from industrialization towards an information-based society. These changes had profound effects upon a broad spectrum of knowledge leading to suggestions of a new form of cultural. Some Universities in the world have developed open universities, employing audio and video tapes, television, satellites, teleconferencing, and telephone tutors. The future of countries often lies within their ability to compete in a global market where industrial based economies are giving way to knowledge based industries, realizing the importance of knowledge, skills and the intellectual capacity to meet the challenges of accelerated change and uncertainty. By means of information technology, education can thus be made available to the students where are located in different places at any time. As a result, education in this way can be unlimited. The exams and grades are gradually becoming available through electronic means and notebooks are starting to give way to laptops. Also, students can be examined through computer managed learning systems and do tutorial exercises on a computer rather than in a classroom. Subsequently, information technology is foreseeing a change in the education environment towards a reliance on electronic sources to deliver material